Water-energy-food nexus tools in theory and practice: a systematic review - Taguta, C.; Senzanje, A.; Kiala, Z.; Malota, M.; Mabhaudhi, Tafadzwanashe (Frontiers Media, 2022)
Sector-based resource management approaches partly contribute to the insecurities in water, energy and food sectors and resources. These approaches fail to acknowledge and capture the interlinkages between these connected resources, a key strength in the water-energy-food (WEF) nexus approach. However, the multi-centric, multidimensional, and spatiotemporally dynamic WEF nexus is complex and uncertain, thus requiring dedicated tools that can unpack it. Various sources have blamed the slow uptake and practical implementation of the WEF nexus on the unavailability of appropriate tools and models. To confirm those claims with evidence, literature on WEF nexus tools was searched from Scopus and Web of Science and systematically reviewed using the PRISMA protocol. It was found that the WEF nexus tools are being developed increasingly, with a current cumulative number of at least 46 tools and models. However, their majority (61%) is unreachable to the intended users. Some available tools are in code format, which can undermine their applicability by users without programming skills. A good majority (70%) lack key capabilities such as geospatial features and transferability in spatial scale and geographic scope. Only 30% of the tools are applicable at local scales. In contrast, some tools are restricted in geographic scope and scale of application, for example, ANEMI 3 and WEF models for large and household scales, respectively. Most (61%) of the tools lack wide application in actual case studies; this was partly attributed to the tools not being readily available. Thus, efforts should be made to disseminate and ensure end-users’ uptake and application of developed tools. Alternatively, the user-friendly tools should be developed on-demand as requested and inspired by potential clients. Developers should consider utility, transferability and scalability across uses and users when improving existing tools and developing new tools so that they are adaptable, only requiring new, specific location-adapted inputs and data. Where and when it is necessary to capture spatial dynamics of the WEF nexus, tools should be geographic information system (GIS)-enabled for automatic WEF nexus location selection, geospatial mapping, and visualization. Such GIS-enabled WEF nexus tools can provide a bird’s eye view of hotspots and champions of WEF nexus practices.